Chromatographic characterization of amphiphilic di‐ and tri‐block copolymers of poly(ethylene oxide) and poly(ε‐caprolactone). Issue 17 (25th July 2018) - Irfan, Muhammad; Bhayo, Adnan Murad; Musharraf, Syed Ghulam; Malik, Muhammad Imran
Abstract: Amphiphilic di‐ and tri‐block copolymers based on poly(ethylene oxide) as a hydrophilic segment and poly(ε‐caprolactone) as a hydrophobic part are synthesized by the ring‐opening polymerization of ε‐caprolactone while using poly(ethylene glycol)s and methoxy poly(ethylene glycol)s of varying molar masses as macro‐initiators. The synthesized block copolymers are characterized with respect to their total relative molar mass and its distribution by size exclusion chromatography. Liquid chromatography at critical conditions of both blocks is established for the analysis of individual block lengths and tracking presence of unwanted homopolymers of both types in the block copolymer samples. New critical conditions of polycaprolactone on reversed phase column are reported using organic mobile phase. The established critical conditions of polycaprolactone extended the applicable molar mass range significantly compared to already reported critical conditions of polycaprolactone in aqueous mobile phase. Block copolymers are also analyzed at critical conditions of poly(ethylene glycol). Complete analysis of the di‐ and tri‐block copolymers at corresponding critical conditions provided a fair estimate of molar mass of non‐critical block besides information regarding presence of homopolymers of both types in the samples.